THE ROLE OF VERBS FOR COMMUNICATION (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This article provides an in-depth exploration of English verbs, including their types, grammatical functions, tenses, aspects, and roles in communication. It discusses the importance of verbs in structuring sentences and conveying meaning, offering practical examples to illustrate their use in both written and spoken English. The article also highlights how verb choice varies depending on context and how strong, expressive verbs can enhance clarity and emotional impact.